Perancangan Sistem Presensi Online Berbasis Granted Validitas Data - M. Mahaputra Hidayat; Bintang Prasetyo Budi Utomo; Muhammad Ivan Zacharia; Achmad Alfan Mubarrok (Informatics Study Program, Faculty of Engineering and Computers, Baturaja University, 2023)
The manual attendance system used by the company suffers from inaccuracies and fraud. Therefore, this study aims to overcome this problem by designing and implementing an online presence system based on granted data validity. Information system development methods are used to design online presence systems that use blockchain technology to ensure data validity and reduce the risk of fraud. In conclusion, an online presence system based on granted data validity can be an effective and efficient alternative solution for institutions that still use a manual attendance system.